Prognostic and diagnostic value of moderate intensity stress test with blood pressure control - Marchenko, V. N.; Noskin, L. A.; Pivovarov, V. V.; Zaytsev, G. K. (Uchenye zapiski (Sankt-Peterburgskiĭ gosudarstvennyĭ medit͡s︡inskiĭ universitet im. akad. I.P. Pavlova), 2014)
In spite of age and blood pressure values at rest,hypertensive response to moderate intensity stress testingis characterized by increasing ofprobable beginning of cardiac infarction, stroke or coronary disease in 1.36 times. The hypertensive response to stress test in people with normal blood pressure values at rest (independent of other risk factors) is characterized by increasing risk of future hypertension more than in 2 times. Antihypertensive drugs affect blood pressure values differently during the stress testing. The prognosis of blood pressure values during daily physical activity is necessary for antihypertensive treatment. Low availability of convenient instruments and methodological tools for continuous measurement of blood pressure (similar to Spiroarteriocardiorhythmograph, Finapres) duringthe dosed physical loads constrain wide use of stress tests with controlled blood pressure in medical practice.